Adherence of Health Care Workers to Personal Protective Equipment During Coronavirus Disease 2019 Pandemic. Issue 6 (November 2020) - Alabbood, Majid
Abstract : Background: An outbreak of a novel corona viral pneumonia started in China late 2019. World Health organization on March 11 declared coronavirus disease 2019 (COVID-19) a pandemic. In China, an estimated 3000 health care workers (HCWs) have been infected. The Centers for Disease Control and Prevention released recommendations for the use of personal protective equipment when treating patients with COVID-19 to minimize the risk of acquiring infection among HCWs. This study aimed to assess adherence of HCWs in Iraq to personal protective equipment during COVID-19 pandemic. Methods: This was an online survey of a group of Iraqi doctors regarding their adherence to personal protective equipment. Results: Most of the surveyed physicians (120) adequately follow the recommendations regarding their personal hygiene, use of masks/respirators, and wearing equipment while providing care for suspected or confirmed cases of COVID-19. However, 11% and 16% do not follow the recommendations while caring for COVID-19 cases and performing aerosol-generating procedures, respectively. Majority of the respondents admit the importance of these measures in lowering the risk of infection. Approximately, two third of the participants started the measures at the beginning or the middle of the outbreak. Conclusions: Most of Iraqi heath care workers involved in the survey follow the recommendations regarding personal protective equipment.